EFEKTIVITAS PROGRAM UPSUS PADI TERHADAP KEBERHASILAN RUMAH TANGGA PETANI (Studi Kasus Di Desa Waiketam Baru Kecamatan Bula Barat Kabupaten Seram Bagian Timur) - Rumadaul, Asis; Girsang, Wardis; Timisela, Natelda R (JURNAL AGRICA, 2024)
The Pajale Special Efforts Program (Upsus) is intended to achieve food self-sufficiency by increasing the production of rice, corn and soybeans in the centers producing these three commodities. Through the UPSUS Pajale program, there is a huge opportunity to overcome the problem of food security.This research aims to analyze the level of production and income of farmers from the UPSUS Pajale program and the factors that influence it. The research took place in Waiketan Baru Village, West Bula District, Eastern Seram Regency. The research location was determined using purposive sampling, on the grounds that farmers in the location were very intensive in carrying out the UPSUS rice program and there was an increase in production and income. The total sample of farmers was 100 respondents. Research data analysis uses production and income analysis, regression analysis to analyze factors that influence farmers' production and income. The research results show that the average lowland rice production in Waiketam Baru village is 4608 kg/ha or 4,608 toh/ha. The total income from rice farming is Rp. 4,092,751/MT. The results of the regression analysis show that the factors that influence production include the amount of urea fertilizer, the amount of NPK fertilizer, medicines, the number of dependents and the number of workers per year have a significant effect on production. The results of the regression analysis show that factors that influence income include the price of urea fertilizer, production quantity, depreciation costs and labor costs that influence farmer income. The results of the index number analysis show that the effectiveness of implementing the Upsus Pajale program for urea fertilizer with an index number of 75.74; NPK fertilizer was 72.34 and seeds were 72.8. The index number value above is in the high category, meaning that the implementation of the Upsus Pajale program really helps farmers in increasing their income and welfare.